Performance analysis of modified residential PV system configuration under mismatch conditions - Subhash Murkute; Vandana A. Kulkarni (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
Partial shading is a prevalent phenomenon with a substantial impact on PV system performance. Various techniques, such as maximum power tracking (MPPT), PV module interconnection, and power electronics-based schemes, have been employed to address these challenges at both the module level and the submodule level. Existing methods face limitations related to the cost of hardware and the complexity of control systems. These limitations hinder the widespread application of current solutions. Also, Module-level techniques though simple and economical provide limited granularity. The choice between these techniques involves a trade-off between complexity, cost, adaptability, and the specific characteristics of the PV system and its operating environment.This paper presents a new hybrid submodule-level partial shading mitigation scheme based on TCT interconnection and differential power processing. The proposed system, emphasizing its role in enhancing overall PV system performance offers a cost-effective, and easy-to-control solution. To compare and validate the performance of proposed hybrid architecture, a practically installed single-phase grid tied central inverter 3 kW residential PV system is considered. This practical PV system is modified to hybrid architecture and the performance parameters such as power generation, mismatch power loss, fill factor, power conversion efficiency and power improvement calculated for different operating conditions. The results show that the modified conventional PV system mitigate the mismatch issue effectively and improves the output performance for any operating condition